1989
DOI: 10.1002/ijc.2910430318
|View full text |Cite
|
Sign up to set email alerts
|

Use of the membrane invasion culture system (mics) as a screen for anti‐invasive agents

Abstract: The Membrane Invasion Culture System (MICS) assay was adapted for relatively rapid screening of compounds and used to identify anti-invasive drugs that inhibit human and murine tumor cell migration through a reconstituted basement membrane in vitro. Cell lines demonstrating low and high invasive and metastatic potentials were tested with all compounds for tumoricidal effects prior to evaluation in MICS at non-cytotoxic doses. The effect on invasive potential in the MICS assay was determined in 3 categories: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…Total number of invading cells was calculated based upon the surface area per high-power field and the surface area of the Minifold-well. Percent invasion was then calculated as described (32 added concomitantly with TGF-,8 to MTLn3 cells, the number of lung colonies was similar to controls, indicating that the metastasis-enhancing factor was, indeed, TGF-P (Fig. 1).…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Total number of invading cells was calculated based upon the surface area per high-power field and the surface area of the Minifold-well. Percent invasion was then calculated as described (32 added concomitantly with TGF-,8 to MTLn3 cells, the number of lung colonies was similar to controls, indicating that the metastasis-enhancing factor was, indeed, TGF-P (Fig. 1).…”
Section: Methodsmentioning
confidence: 75%
“…To measure tumor cell invasion, the membrane invasion culture system (MICS) (32,33) was used with minor modifications. Instead of the 12/15 well configuration used in the original MICS, we used a 24-well manifold chamber fitted with a silicon gasket between the upper and lower plates to ensure no lateral crosscontamination between wells (Neuroprobe, Cabin John, MD).…”
Section: Methodsmentioning
confidence: 99%
“…This model was optimized to fit the needs of individual laboratories and to run several samples at the same time, and it has been adapted to commercial packages. Screening systems, first employed by Mary Hendrix as the MICS assay (8), are also commercially available.…”
Section: The Present and Future Perspectivesmentioning
confidence: 99%
“…While a few reports indicate that paclitaxel exposure increases motility and invasion (Welch et al, 1989;Silbergeld et al, 1995), others indicate an inhibitory effect on invasion (Westerlund et al, 1997;Sgadari et al, 2000). Silbergeld et al (1995) reported that increasing the paclitaxel concentration caused increased locomotion in glioblastoma cell lines.…”
mentioning
confidence: 99%
“…Silbergeld et al (1995) reported that increasing the paclitaxel concentration caused increased locomotion in glioblastoma cell lines. Welch et al (1989) showed that pretreatment of cell lines, with low and high invasive potentials, with vincristine, colcemid, or colchicine (but not paclitaxel), at noncytotoxic levels, resulted in inhibition of invasion. Westerlund et al (1997) showed that OVCAR-3 cell attachment, migration and in vitro invasion were significantly decreased after paclitaxel treatment.…”
mentioning
confidence: 99%